Access to Enantiopure Triarylmethanes and 1, 1‐Diarylalkanes by NHC‐Catalyzed Acylative Desymmetrization. Issue 10 (25th January 2017) - Lu, Shenci; Song, Xiaoxiao; Poh, Si Bei; Yang, Hui; Wong, Ming Wah; Zhao, Yu
Abstract: We present herein an unprecedented, efficient and enantioselective synthesis of triarylmethanes and 1, 1‐diarylalkanes through N‐heterocyclic carbene‐catalyzed acylative desymmetrization of bisphenols. This method utilizes readily available substrates, reagents and a simple procedure to deliver the valuable products in excellent enantiopurity. DFT calculations reveal that the selectivity is governed by the C−C bond cleavage step of the tetrahedral intermediate leading to the ester product. A transition state model featuring a combination of intramolecular hydrogen bond and steric effect is developed to explain the enantioselectivity. Abstract : Three′s the charm : We present herein a general, efficient and enantioselective synthesis of triarylmethanes and 1, 1‐diarylalkanes through N‐heterocyclic carbene‐catalyzed acylative desymmetrization of bisphenols. This method utilizes readily available substrates, reagents and a simple procedure to deliver the valuable products in excellent enantiopurity. DFT calculations provided a transition‐state model featuring a combination of intramolecular hydrogen bond and steric effect to explain the enantioselectivity.